LOKAKARYA PENDAMPINGAN DAN SOSIALISASI DISIPLIN POSITIF SEKOLAH PENGGERAK ANGKATAN 1 KABUPATEN SIDOARJO - Lestariningsih; Dewi Sukriyah; SITI NURIYATIN (STKIP PGRI Sidoarjo, 2024)
These workshops and outreach aim to teach teachers, parents, and community leaders techniques and strategies for building an environment that supports children's development in a positive way. This activity was carried out in Sidoarjo Regency with 27 participants consisting of 27 teachers, school principals and supervisors. Methods in this activity include training, socialization, discussion and questionnaires. The results of this activity show that participants gave a positive response to the workshop and were positive discipline.